Impact of school‐based dental program performance on the oral health‐related quality of life in children. Issue 1 (27th July 2015) - Amalia, Rosa; Schaub, Rob M. H.; Stewart, Roy E.; Widyanti, Niken; Groothoff, Johan W.
Abstract: Objective: To assess the association between the performance of school‐based dental programs (SBDPs) and oral health‐related quality of life (OHRQoL) in school children, in the province of Yogyakarta, Indonesia, taking into account untreated caries and sociodemographic factors. Methods: A cross‐sectional survey was administered with 1906 children aged 12 and participating in SBDPs. Four SBDPs were chosen to represent good and poor performance in urban and rural areas. Caries was assessed using World Health Organization (WHO) criteria, whereas the children were interviewed for the OHRQoL and sociodemographic data. The OHRQoL was assessed using the Condition‐Specific Child‐Oral Impact on Daily Performances (CS Child‐OIDP) index related to dental caries. Results: The mean CS Child‐OIDP score was 1.63 (SD ± 3.20) for good performance SBDP and 6.89 (SD ± 8.85) for poor performance SBDP. Analysis by negative binomial regression showed that being served by a poorly performing SBDP (RR = 4.45, 95% CI = 3.87–5.13), and to some extent living in a rural area and being a girl, were significantly associated with a greater risk of having a lower quality of life than were the counterparts. Untreated caries did not show an association with OHRQoL. Conclusion: There are substantial indications that SBDP performance is related to children's OHRQoL.